2018
DOI: 10.1155/2018/8436948
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fluoroquinolones in Pharmaceutical Formulations by Extractive Spectrophotometric Methods Using Ion-Pair Complex Formation with Bromothymol Blue

Abstract: In this paper, we reported a new, simple, accurate, and precise extractive spectrophotometric method for the determination of fluoroquinolones (FQs) including ciprofloxacin (CFX), levofloxacin (LFX), and ofloxacin (OFX) in pharmaceutical formulations. The proposed method is based on the ion-pair formation complexes between FQs and an anionic dye, bromothymol blue (BTB), in acidic medium. The yellow-colored complexes which were extracted into chloroform were measured at the wavelengths of 420, 415, and 418 nm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Table 6 also indicates that the well-fitting of As(V) adsorption resulting from the pseudo-second-order model yielded very high determination coefficients ( R 2 > 0.99) as compared with the pseudo-first order plot. It also indicated that the chemisorption as the rate-limiting mechanism took place during the adsorption by FAC surface rather than physisorption [ 2 , 5 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 also indicates that the well-fitting of As(V) adsorption resulting from the pseudo-second-order model yielded very high determination coefficients ( R 2 > 0.99) as compared with the pseudo-first order plot. It also indicated that the chemisorption as the rate-limiting mechanism took place during the adsorption by FAC surface rather than physisorption [ 2 , 5 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…At that time, it was named product of Jabir, an odorless, tasteless toxic that could kill people very quickly without leaving any trace in the human body [ 3 , 4 ]. The median lethal dose of LD 50 (50% of laboratory tested animals have died) of arsenic is 763 mg per kilogram of body weight (via diet) and 13 mg per kilogram of body weight (via injection) [ 5 ]. However, arsenic is still not as toxic as its oxidizing compounds, such as arsenic trioxide (As 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 In the field of inorganic analysis, many previously addressed articles extensively discussed the mode of formation, the sensitivity and selectivity improvement of both ternary complex types. 9,10 However, to enhance the sensitivity of organic complex system, a binary ion-pair complex was formed by producing organic compound-organic dye interaction, 11,12 but this method is convoluted and requires an extraction procedure. The previously documented methods for the determination of GFX included different spectroscopic and separation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of APP is challenging because of the emergence of drug-resistant phenotypes and various drug resistance mechanisms [ 3 ]. Fluoroquinolones are important antibiotics used to treat gram-negative bacterial infections in both human and veterinary medicine [ 4 ]; however, therapeutic options against APP are limited by the emergence of quinolone-resistant strains [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%